2021
DOI: 10.1016/j.celrep.2021.109071
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Wnt ligand inhibition overcomes key tumor-mediated resistance pathways to anti-PD-1 immunotherapy

Abstract: SUMMARY While immune checkpoint blockade is associated with prolonged responses in multiple cancers, most patients still do not benefit from this therapeutic strategy. The Wnt-β-catenin pathway is associated with diminished T cell infiltration; however, activating mutations are rare, implicating a role for autocrine/paracrine Wnt ligand-driven signaling in immune evasion. In this study, we show that proximal mediators of the Wnt signaling pathway are associated with anti-PD-1 resistance, and pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 82 publications
(143 reference statements)
4
49
0
Order By: Relevance
“…Our result found a positive correlation between the expression of this gene and longer survival. A recent study emphasized the function of Wnt/β catenin activation in immunotherapy resistance [ 34 ]. Therefore, we analyzed the prediction power of the signature in immunotherapy response.…”
Section: Discussionmentioning
confidence: 99%
“…Our result found a positive correlation between the expression of this gene and longer survival. A recent study emphasized the function of Wnt/β catenin activation in immunotherapy resistance [ 34 ]. Therefore, we analyzed the prediction power of the signature in immunotherapy response.…”
Section: Discussionmentioning
confidence: 99%
“…We have to note here two smaller studies with metastatic melanoma samples which were published under the NCBI GEO accession numbers GSE123728 [ 77 ] and GSE165745 [ 78 ] with 13 and 24 patients, respectively. Both studies administered anti-PD-1 monotherapy (pembrolizumab or nivolumab) and determined gene expression using the NanoString nCounter platform from FFPE samples.…”
Section: Malignant Melanoma Datasets With Anti-pd-1 Monotherapymentioning
confidence: 99%
“…Preliminary data confirmed that treatment with WNT inhibitors were able to revert the immune suppressive conditions ( 83 , 84 ) and could also enhance response to different immunotherapeutic approaches ranging from adoptive transfer to ICPi. The tumor rejection was correlated both to changes in the tumor cells, like an upregulation of MHC class I surface expression ( 85 ) and modulation of PD-L1 expression ( 86 ) that render tumor cells more sensitive to cytotoxic T lymphocytes (CTLs) as well as to alterations in the TME, which reverted the immune suppressive conditions and allowed recruitment of effector cells ( 87 , 88 ).…”
Section: Oncogenic and Tsg Pathways In Tumors Influence The Frequency...mentioning
confidence: 99%